Yerba Mate Modulates Tumor Cells Functions Involved in Metastasis in Breast Cancer Models - Rocio Soledad, Garcia-Lazaro; Lorena Gisel, Caligiuri; Norailys, Lorenzo; Humberto, Lamdan; Daniel Fernando, Alonso; Hernan Gabriel, Farina (Frontiers in Pharmacology, 2021)
Breast cancer (BC) is the most frequent cancer in women and tumor metastasis is a major cause of cancer-related deaths. Our aim was to evaluate anti-metastatic properties of yerba mate extract (YMe) in BC models. 4T1, F3II, MCF-7 and MDA-MB231 cell lines were used to perform in vitro assays. The F3II syngeneic mammary carcinoma model in BALB/c mice was used to evaluate tumor progression, BC metastasis and survival. Cells were inoculated subcutaneously into the flank for the heterotopic model and into the mammary fat pad for the orthotopic model. YMe was administered p.o. in a dose of 1.6 g/kg/day. In vitro YMe inhibited cell proliferation and reduced tumor cell adhesion, migration and invasion. These biological effects were cell-line dependent. In vivo YMe reduced tumor metastasis and increased mice survival in both models. Our preclinical results suggest that YMe could modulate tumor progression and metastasis in BC models.